2015
DOI: 10.1093/annonc/mdv065
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II–III study of bevacizumab in combination with chemotherapy in previously untreated extensive small-cell lung cancer: results from the IFCT-0802 trial

Abstract: Administering 7.5 mg/kg Bev after induction did not improve outcome in extensive SCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 9 publications
0
57
1
Order By: Relevance
“…One of these trials involved in ziv-aflibercept plus CT versus CT [16]; two bevacizumab plus CT versus CT [17, 18]; six rh-Endostatin plus CT versus CT [19–24]; six thalidomide plus CT versus CT [25–30]; one vandetanib plus CT versus CT [31]. The populations were comparable with respect to demographics, clinical parameters, stage at initial diagnosis in different clinical settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these trials involved in ziv-aflibercept plus CT versus CT [16]; two bevacizumab plus CT versus CT [17, 18]; six rh-Endostatin plus CT versus CT [19–24]; six thalidomide plus CT versus CT [25–30]; one vandetanib plus CT versus CT [31]. The populations were comparable with respect to demographics, clinical parameters, stage at initial diagnosis in different clinical settings.…”
Section: Resultsmentioning
confidence: 99%
“…These results were summarized in Table 1. Among these 16 trials, two were phase III clinical trials [29, 30]; one phase II- III trial [18]; four phase II trials [16, 17, 19, 31] while nine studies did not mention a trial phase [20–28]. Outcomes included ORR, OS, PFS and severe adverse events (AEs, Grade≥3).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of adverse events, there was a high rate of severe phlebitis. Several studies have reported that bevacizumab has enhanced the toxicity and increased the activity of another agent in a combination regimen (22,23). Bevacizumab targets VEGF and alters tumor vessel physiology, thereby increasing intratumoral drug uptake (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized phase II/III trial it was reported that Bev alone after induction chemotherapy did not improve outcome in ED-SCLC patients. 21 Recent studies have been conducted to investigate innovative agents combined with chemotherapy in patients with ED-SCLC. However, specifically, no significant improvement in response rates, PFS, and OS were reported with chemotherapy with rh-endostatin, with carboplatin/E with the small-molecule B-cell lymphoma 2 (Bcl-2) inhibitor obatoclax, with P and amrubicin, nor with platinum-based chemotherapy and the sarcoma-kinase inhibitor saracatinib.…”
Section: Discussionmentioning
confidence: 99%